miRNA and mRNA Signatures in Human Acute Kidney Injury Tissue - Janosevic, Danielle; De Luca, Thomas; Melo Ferreira, Ricardo; Gisch, Debora L.; Cheng, Ying-Hua; Hato, Takashi; Luo, Jinghui; Yang, Yingbao; Hodgin, Jeffrey B.; Phillips, Carrie L.; Dagher, Pierre C.; Eadon, Michael T. (The American journal of pathology, 2025)
Acute kidney injury (AKI) is an important contributor to the development of chronic kidney disease (CKD). There is a need to understand molecular mediators that drive recovery and progression to CKD. In particular, the regulatory role of miRNAs in AKI is poorly understood. Herein, miRNA and mRNA sequencing were performed on biobanked human kidney tissues obtained during the routine care of subjects with a diagnosis of AKI, minimal change disease, or on nephrectomy tissue with no known kidney disease. mRNA analysis revealed that nephrectomy tissues exhibited an injury signature similar to that of AKI which was not identified in minimal change disease samples. The transcriptomic signature of human AKI was enriched in pathways involved in cell adhesion, epithelial-to-mesenchymal transition, and cell cycle arrest (eg, CDH6, ITGB6, CDKN1A). In AKI, up-regulation of miR-146a, miR-155, miR-142, and miR-122 was associated with pathways involved in immune cell recruitment, inflammation, and epithelial-to-mesenchymal transition. miR-122 and miR-146 were associated with down-regulation of DDR2 and IGFBP6, which are genes involved in the recovery and progression of kidney disease. These data provide integrated miRNA signatures that complement mRNA and other epigenetic data available in kidney atlases. [Display omitted]